2011
DOI: 10.1097/fjc.0b013e31822b7204
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Stimulation, Through its Nicotinic Action, Limits Infarct Size and the Inflammatory Response to Myocardial Ischemia and Reperfusion

Abstract: Vagal activity has protective effects in ischemic heart disease. We tested whether vagal stimulation (VS) could modulate the inflammatory reaction, a major determinant of cardiac injury after ischemia/reperfusion. Four groups of male rats underwent myocardial ischemia (30 minutes) and reperfusion (24 hours). One group underwent VS (40 minutes), 1 VS plus atrial pacing (VS + Pacing), and 1 VS plus nicotinic inhibition by mecamylamine (VS + MEC). After 24 hours, the area at risk, infarct size, inflammation param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
136
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 26 publications
6
136
0
2
Order By: Relevance
“…Heart rate-independent effects may include anti-adrenergic effects at ventricular level due to sympathetic-parasympathetic interaction, anti-apoptotic effects and the anti-inflammatory reflex postulated by Tracey [19]. In a model of ischaemia reperfusion in rats, vagal stimulation markedly reduced infarct size and markers of inflammation without changes in heart rate [20].…”
mentioning
confidence: 98%
“…Heart rate-independent effects may include anti-adrenergic effects at ventricular level due to sympathetic-parasympathetic interaction, anti-apoptotic effects and the anti-inflammatory reflex postulated by Tracey [19]. In a model of ischaemia reperfusion in rats, vagal stimulation markedly reduced infarct size and markers of inflammation without changes in heart rate [20].…”
mentioning
confidence: 98%
“…5,6 Evidence is accumulating that vagal nerve activity exerts an immunomodulatory influence, characterized by an anti-inflammatory effect that may be beneficial in a variety of cardiovascular disease states, including myocardial infarction and heart failure. [6][7][8] Indeed, vagal nerve stimulation (VNS) has been reported to limit infarct size in a variety of experimental studies (see Table 4 of Uitterdijk et al 6 ). The exact mechanism by which VNS exerts its cardioprotective effect is not fully understood, but includes nicotinic 8 and muscarinic 7 receptor stimulation as well as activation of nitric oxide synthase, 6 while the VNS-associated bradycardia does not appear to be mandatory for its cardioprotective effects.…”
Section: In This Issue Of Actamentioning
confidence: 99%
“…[6][7][8] Indeed, vagal nerve stimulation (VNS) has been reported to limit infarct size in a variety of experimental studies (see Table 4 of Uitterdijk et al 6 ). The exact mechanism by which VNS exerts its cardioprotective effect is not fully understood, but includes nicotinic 8 and muscarinic 7 receptor stimulation as well as activation of nitric oxide synthase, 6 while the VNS-associated bradycardia does not appear to be mandatory for its cardioprotective effects. [6][7][8] In the present issue of Acta Physiologica, Kiss et al…”
Section: In This Issue Of Actamentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies demonstrated that vagal nerve stimulation 49, 50 mimicked the cardioprotective effect of RIC, whereas with bilateral vagotomy this was abrogated 49, 50. An elegant study by Mastitskaya et al.…”
Section: Ric: History and Evolutionmentioning
confidence: 99%